Undifferentiated Adipose Tissue Stem Cell Transplantation Promotes Hepatic Regeneration, Ameliorates Histopathologic Damage of the Liver, and Upregulates the Expression of Liver Regeneration- and Liver-Specific Genes in a Rat Model of Partial Hepatectomy. (14th March 2018) - Apostolou, Konstantinos G.; Papanikolaou, Ioannis G.; Katselis, Charalampos; Feretis, Themistoklis; Kletsas, Dimitrios; Konstadoulakis, Manousos M.; Lymperi, Maria; Saetta, Angelica A.; Tsikalakis, Spiros; Agrogiannis, George; Patsouris, Efstratios; Zografos, George C.; et al.
Abstract : Objective. Adipose tissue stem cells (ADSCs) present a promising therapeutic method to alleviate liver failure (LF). The purpose of this prospective study was to evaluate the efficacy of undifferentiated ADSC transplantation on liver regeneration and on the expression of liver regeneration- and liver-specific genes, following 60% partial hepatectomy (PHx). Methods. Sixty female rats were subjected to PHx and were transplanted with 10 6 or 2 × 10 6 ADSCs, either into the portal vein (PV) or into the hepatic parenchyma. Animals of the control group were not transplanted and served as controls. Animals were sacrificed on the 4th, the 7th, or the 15th postoperative day (POD). Results. The transplanted ADSCs were successfully engrafted into the liver parenchyma and ameliorated the histopathologic damage on the 7th and 15th POD. All transplanted animals demonstrated a significantly higher liver regeneration rate on the 4th and 7th POD, compared with the control group. The expression of hepatocyte growth factor, α -fetoprotein, tyrosine aminotransferase, hepatocyte nuclear factor 4a, and cytochrome P450 1A2 was significantly upregulated, compared with the control group. Conclusions. Although undifferentiated, ADSC transplantation significantly enhanced the liver regeneration process. These findings may be proven clinically valuable, especially in cases of acute LF.